Depression in Patients With End-Stage Renal Disease Presenting to a Tertiary Care Hospital, Hyderabad - Raheela, .; Das, Bhagwan; Zubaida, .; Minhas, Maimoona Habib; Memon, Asfa; Qadir, Abdul (Biological and Clinical Sciences Research Journal, 2025)
The psychological disorders that are most prevalent in end-stage renal disease (ESRD) patients receiving hemodialysis are anxiety and depression. The prevalence of these disorders is affected by patient characteristics such as the burden of chronic illness, limitations in daily functioning, changes in body image, financial strain, and the emotional toll of managing a life-threatening condition. Objective: To evaluate the frequency of depression in patients with ESRD presenting to a tertiary care hospital. Methodology: A cross-sectional descriptive study conducted at the Nephrology Department, Liaquat University Hospital, Hyderabad, from 27th Feb to 26th May 2025. ESRD had been on hemodialysis two to three times a week for the past three months or longer; both males and females were included. Those who have had a prior history of depression before ESRD, experienced a recent loss of a close family member, or had undergone any recent significant adverse life events were excluded. The Hospital Anxiety and Depression Scale (HADS) was used to assess depression, and a score of 11 or above was classified as indicative of depression. Result: A total of 100 participants were included, with a mean age of 50.14 ± 11.23 years. The participant composition was 57% male and 43% female. Approximately 71% of participants had a dialysis duration of less than three months, while 29% had a duration of more than three months. The underlying causes of ESRD in the study population show 37 (37%) had an unknown cause, followed by 26 (26%) of participants had diabetes,17 (17%) had stone disease, 14 (14%) had hypertension, 5(5%) had polycystic kidney disease and 1 (1%) chronic glomerulonephritis (GN). Of the 100 participants, 59% were found to have depression, and the remaining 41% of participants did not. Conclusion: The study highlights a high prevalence of depression among individuals with ESRD, significantly exceeding that of the general population. Depression rates were unaffected by gender or socio-demographics, but were higher among patients who smoked.